2018
DOI: 10.2147/rru.s142989
|View full text |Cite
|
Sign up to set email alerts
|

Redo hypospadias surgery: current and novel techniques

Abstract: Failed hypospadias includes patients with multiple attempts at hypospadias surgery. These present as recurrent stricture, urethrocutaneous fistula glans dehiscence, urethral dehiscence, chordee, and glans deformity. Failed hypospadias is a complex and challenging issue. Various surgeries and techniques have been described for hypospadias. We need uniform guidelines for management of failed hypospadias. In this paper, we highlight the current and feasible options in the management of failed hypospadias which wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Authors also consider redo urethroplasty as gold standard for recurrent strictures with or without fistula as suggested by other researchers. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Authors also consider redo urethroplasty as gold standard for recurrent strictures with or without fistula as suggested by other researchers. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up of more than 4 years there were nine complications (30%): eight meatal stenoses (five with fistulas) and one isolated fistula. [15] Kulkarni et al [16] reported that determining the type of urethroplasty to be performed depended on the following factors namely scarring of the urethral plate, width of urethral plate, width of glans, degree of chordee and ventral skin. Dorsal inlay graft technique is indicated whenever the urethral plate has been removed and only a strip of grossly healthy skin remained in its place.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, reconstructive surgeons have developed alternative approaches in order to decrease the burden of surgery. 8,9 Nowadays, the correction of ventral penile curvature is usually achieved with dorsal plications preceded by complete NVB mobilisation, without further disassembling. However, even if this approach appears to be less burdensome compared to the total disassembling, complete NVB mobilisation is still associated with a non-negligible risk of complications.…”
Section: Discussionmentioning
confidence: 99%